A Comparative Study on Bioleaching Properties of Various Sulfide Minerals Using Acidiphilium cryptum - Cho, Kang Hee; Kim, Hyun Soo; Lee, Chang Gu; Park, Seong Jik; Choi, Nag Choul (Applied Sciences (Switzerland), 2023)
Bioleaching has been regarded as a green alternative to chemical leaching in metal extraction processes. In this study, the bioleaching properties of indigenous acidophilic bacteria for various sulfide minerals were compared and evaluated in terms of pH reduction and metal leaching. The primary minerals in the samples were sphalerite (ZnS) (SP), galena (PbS) (GN1 and GN2), pyrite (FeS2) (PY), and chalcopyrite (CuFeS2) (CCP), and an indigenous acidophilic bacterium, Acidiphilium cryptum (99.56%), was applied for bioleaching experiments. The metal extraction in bioleaching differed according to the mineral content. The leached metal concentration of Zn was higher than that of Pb for the SP sample with a high ZnS content, whereas the concentration of Pb was higher than that of Zn for the GN1 and GN2 samples with a high PbS content. Meanwhile, the leaching rate of Zn was faster than that of Pb for all samples. Corrosion action was observed on the surface of bacterial residues in SP and GN1 samples. These results show that the bioleaching mechanism based on sulfide minerals proceeds through indirect biological oxidation, chemical oxidation, and direct bacterial oxidation. The results of this study can provide basic research data for process optimization when employing bioleaching to extract valuable metals.
Keywords: bioleaching; metal leaching; pH reduction; reduction rate; sulfide mineral